Could the central‐eastern Iberian Mediterranean region be defined as a refugium? Fauna and flora in MIS 5–3 and their implications for Palaeolithic human behaviour. (9th March 2021) - Real, Cristina; Martínez‐varea, Carmen María; Carrión, Yolanda; Badal, Ernestina; Sanchis, Alfred; Guillem, Pere; Martínez‐valle, Rafael; Villaverde, Valentín
ABSTRACT: Neanderthals and modern humans from the Early Upper Palaeolithic had a highly developed knowledge of their environment, where they found the essential resources for their subsistence. Therefore, changes in the local landscape and available resources should have influenced their behaviour, as indicated by faunal and plant remains recovered from archaeological sites. In the central‐eastern Iberian Mediterranean region, the archaeological sites of Cova Negra, Abrigo de la Quebrada, Cova de les Malladetes and Cova de les Cendres have provided wood charcoal, seeds and fauna. The combination of these data allows an accurate reconstruction of the regional landscape from MIS 5 to the beginning of MIS 2. The available evidence suggests that this region could be defined as a refugium in which biodiversity persisted. This type of refugium, containing a high diversity of biotopes and some endemic species, which has lasted until the present day, can be seen at a regional scale, but also locally, especially near the coast. These special characteristics of the region – relatively stable climatic conditions with oscillations mainly in aridity and humidity, and a high diversity of flora and fauna – could explain the high density of Palaeolithic sites throughout Middle and Upper Palaeolithic here.